A Promising IFN-Deficient System to Manufacture IFN-Sensitive Influenza Vaccine Virus - Chen, Can; Fan, Wenhui; Li, Jing; Zheng, Weinan; Zhang, Shuang; Yang, Limin; Liu, Di; Liu, Wenjun; Sun, Lei (Frontiers in Cellular and Infection Microbiology, 2018)
Interferon (IFN)-sensitive and replication-incompetent influenza viruses are likely to be the alternatives to inactivated and attenuated virus vaccines. Some IFN-sensitive influenza vaccine candidates with modified non-structural protein 1 (NS1) are highly attenuated in IFN-competent hosts but induce robust antiviral immune responses. However, little research has been done on the manufacturability of these IFN-sensitive vaccine viruses. Here, RIG-I-knockout 293T cells were used to package the IFN-sensitive influenza A/WSN/33 (H1N1) virus expressing the mutant NS1 R38A/K41A. We found that the packaging efficiency of the NS1 R38A/K41A virus in RIG-I-knockout 293T cells was much higher than that in 293T cells. Moreover, the NS1 R38A/K41A virus almost lost its IFN antagonist activity and could no longer replicate in A549, MDCK, and Vero cells after 3-6 passages. This indicated that the replication of NS1 R38A/K41A virus is limited in conventional cells. Therefore, we further established a stable Vero cell line expressing the wild-type (WT) NS1 of the WSN virus, based on the Tet-On 3G system. The NS1 R38A/K41A virus was able to steadily propagate in this IFN-deficient cell line for at least 20 passages. In a mouse model, the NS1 R38A/K41A virus showed more than a 4-log reduction in lung virus titers compared to the WT virus at 3 and 5 days post infection. Furthermore, we observed that the NS1 R38A/K41A virus triggered high-level of IFN-α/β production in lung tissues and was eliminated from the host in a relatively short period of time. Additionally, this virus induced high-titer neutralizing antibodies against the WT WSN, A/Puerto Rico/8/1934 (PR8), or A/California/04/2009 (CA04) viruses and provided 100% protection against the WT WSN virus. Thus, we found that the replication of the NS1 R38A/K41A virus was limited in IFN-competent cells and mice. We also presented a promising IFN-deficient system, involving a RIG-I-knockout 293T cell line to package the IFN-sensitive vaccine virus and a stable Vero cell line expressing NS1 to propagate the IFN-sensitive vaccine virus. The IFN-deficient system is applicable for the manufacture of IFN-sensitive vaccine virus.